chain rule

Asked by ashwinikumar59 | 8th May, 2010, 04:17: PM

Expert Answer:

Let y be a function of x.

Chain rule,

dy/dx = (dy/du)(du/dx)               .... multiply and divide by du

y = sinnx  = un  ........... where u = sin x

then dy/du = nun-1

du/dx = cos x

and

dy/dx = (dy/du)(du/dx) = nun-1cos x = nsinn-1x cos x 

Regards,

Team,

TopperLearning.

 

 

Answered by  | 8th May, 2010, 09:01: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.